Lysophosphatidylcholine acts in the constitutive immune defence against American foulbrood in adult honeybees - Riessberger-Gallé, Ulrike (Sci Rep, 2016)
Honeybee (Apis mellifera) imagines are resistant to the Gram-positive bacterium Paenibacillus larvae (P. larvae), causative agent of American foulbrood (AFB), whereas honeybee larvae show susceptibility against this pathogen only during the first 48 h of their life. It is known that midgut homogenate of adult honeybees as well as a homogenate of aged larvae exhibit strong anti-P. larvae activity. A bioactivity-guided LC-HRMS analysis of midgut homogenate resulted in the identification of 1-oleoyl-sn-glycero-3-phosphocholine (LPC) pointing to a yet unknown immune defence in adult honeybees against P. larvae. Antimicrobial activity of LPC was also demonstrated against Melissococcus plutonius, causative agent of European Foulbrood. To demonstrate an AFB-preventive effect of LPC in larvae, artificially reared larvae were supplemented with LPC to evaluate its toxicity and to assess whether, after infection with P. larvae spores, LPC supplementation prevents AFB infection. 10 μg LPC per larva applied for 3 d significantly lowered mortality due to AFB in comparison to controls. A potential delivery route of LPC to the larvae in a colony via nurse bees was assessed through a tracking experiment using fluorescent-labelled LPC. This yet undescribed and non-proteinous defense of honeybees against P. larvae may offer new perspectives for a treatment of AFB without the utilization of classic antibiotics.